The Influence of In-Service Teachers Training Programs on the Professional Development of School Teachers - Qaisra, Rani; Haider, Syed Zubair (Pakistan Journal of Humanities and Social Sciences, 2023)
This study was conducted to find out the impact of in-service teacher training on teachers’ professional development. The survey approach was chosen because it was the most practical and cost-effective way to collect data from such a large population. Questionnaire for this studywas self-developed by the researcher and based on a literature review. Data collected from 1200 participants was analyzed using descriptive and inferential statistics. There were insignificant differences between male and female teachers in training goals, observation, assessment, and evaluation. There were also statisticallyinsignificant differences between districts in how teachers felt about in-service teacher training. School leaders, organizations that train teachers and teacher trainers should put teachers at the center of training programs to get teachers more involved and meet current needs. Financial or other kinds of incentives should be used, and teachers may need to get certification for in-service teacher training to improve their skills.